THE IMPACT OF VILLAGE ONLINE MARKETS ON INCREASING THE INCOME OF SMALL AND MEDIUM ENTERPRISES (MSMES) IN INDONESIA - Saka, Dijan Novia; Efendi, Rofik; Sari, Widya Ratna; Subandono, Agus; Ilham Haq, Muhammad Alfasa (International Journal of Cultural and Social Science, 2026)
This study aims to analyze the impact of village online markets on increasing the revenue of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The development of digital technology has driven changes in consumer shopping behavior, making village online platforms a strategic alternative for MSMEs in expanding market access. The research method used was a quantitative approach, collecting data through questionnaires from MSMEs, and analysis using simple regression/PLS-SEM to test the relationship between the use of village online markets and increased revenue. The results show that village online markets have a positive and significant impact on increasing MSME revenue. The use of digital platforms allows MSMEs to reach a wider range of consumers, reduces marketing costs, and increases the competitiveness of local products. These findings emphasize the importance of strengthening digital literacy and supporting technological infrastructure in villages as key to local economic sustainability.